Characterization, diagnosis and management of plant viruses; Vol.3: vegetable and pulse crops - Rao, G.P.; Kumar, P. Lava; Holguin-Peña, R.J. (2008)
The 3rd in the series "Plant Pathogens: Characterization, Diagnosis and Management", this volume contains 19 chapters on the taxonomy, characterization, diagnosis and management of vegetable and pulse viruses. Topics consisted of: Tospovirus (chapter 1); Cucumber mosaic virus infecting vegetable and pulse crops (2); Potyviruses infecting grain legumes (3); Geminiviruses infecting legumes (4); Pecluviruses (5); Tomato yellow leaf curl virus (6); Pepper golden mosaic virus [Serrano golden mosaic virus] and related Geminiviruses affecting tomato (7); Pepper yellow mosaic virus (8); Tobacco streak virus of vegetable crops (9); virus diseases of chickpea (10); virus diseases of pigeon pea (11); Ilarvirus from cowpea (12); Cucurbit yellow stunting disorder virus (13); Cucurbit aphid-borne yellows virus in Spain (14); Turnip mosaic virus (15); Carrot motley dwarf virus complex (16); viruses associated with the lettuce big-vein disease (17); Pepino mosaic virus (18); and Bhendi yellow vein mosaic virus (19). This book will be useful to everyone interested in plant virology, plant pathology, disease control and plant biology.